In the Footsteps of Kierkegaard - Szewczyk-Haake, Katarzyna (Peter Lang GmbH, Internationaler Verlag der Wissenschaften, 2022)
Cover – Dedication – Table of Contents – Introduction – 1. Contemporary comparative studies and the comparative studies of Swedish and Polish literature – 2. Józef Wittlin and Pär Lagerkvist, or the question of the ethical horizon of modernist literature – 3. Ethical criticism: Notes on the method – Chapter One Modern ethical literature: Genealogy and definition – 1. Moral obligations of literature and changes in ethics in modernity – 2. The shadow of modernisation – 3. Søren Kierkegaard's ethics of communication and the model of ethical literature by Józef Wittlin and Pär Lagerkvist – Kierkegaard's reception in Swedish and Polish literature until the Second World War33 – Kierkegaard's ethics of communication / literary communication – Interpretative context: Kierkegaard and/or Nietzsche – Chapter Two Ethical tasks of literature according to Lagerkvist and Wittlin – 1.
Description based on publisher supplied metadata and other sources
Keywords: Wittlin; Józef; Lagerkvist; Pär; Kierkegaard; Søren; Kierkegaard; Søren - 1813-1855; Lagerkvist; Pär - 1891-1974; Wittlin; Józef - 1896-1976; Expressionism in literature; Ethics in literature; Electronic books; Expressionnisme dans la littérature; Morale dans la littérature; Influence (Literary; artistic; etc.); Criticism; interpretation; etc